Effects of yoga and aerobic exercise on wellbeing in physically inactive older adults: Randomized controlled trial (FitForAge). (June 2022) - Welford, Paul; Östh, Josefine; Hoy, Sara; Diwan, Vinod; Hallgren, Mats
Abstract: Objective: To compare the effects of yoga and aerobic exercise (AE) on wellbeing in physically inactive, but otherwise healthy older adults. A secondary objective was to assess and compare the frequency of adverse events associated with yoga and AE. Design: Twelve-week, three-group, parallel randomized controlled trial with blinded follow-up assessment. Interventions: Participants were supported to complete ≥ 3 Hatha yoga classes/week or ≥ 3 AE sessions/week. A wait-list control (WLC) group continued usual daily activities. Main outcome measure: Change in wellbeing, assessed using the Satisfaction with Life Scale (SWLS) and Life Satisfaction Index-Z (LSI), at baseline and at 12-week follow up. Results: In total, 82 adults (mean age 72.5 years, range 65–85, 77% female) were recruited. Of these, 27 were randomized to yoga, 29 to aerobic exercise and 26 to wait-list control. Medium-magnitude treatment effects (Hedges' g ) were seen for yoga versus WLC and AE versus WLC(SWLS, g = 0.65 and 0.56; LSI, g = 0.54 and 0.54, respectively). In per-protocol analyses, larger effect sizes were found (SWLS, g = 0.72 and 0.66; LSI, g = 0.76 and 0.76, respectively). Adverse events were less frequent in the yoga group (6/27; 22%) compared to AE (10/27; 37%). Conclusions: Among physically inactive older adults, participation in yoga or AE was associated with beneficial effects on subjective wellbeing when compared to a non-active control group. Yoga was associated with fewer injuries and may be especially suitable for older adults (DRKS 00015093). Highlights: Yoga had a positive effect on wellbeing compared to a wait-list control group. Aerobic exercise had a similar positive effect on wellbeing. Injuries were less prevalent in the yoga group compared to aerobic exercise.